Experiences from the teacher-researcher's perspective on learning study: Challenges and opportunities. Issue 1 (3rd January 2017) - Johansson, Patrik; Thorsten, Anja
Abstract : Purpose: The purpose of this paper is to analyze and discuss experiences, in terms of challenges and opportunities, of teacher-researchers who engage in research on the learning study approach. The following two questions will be addressed: how can the teaching experience influence, and become an asset, in the research process and what challenges do teachers face when they enter the research practice? Design/methodology/approach: Each question will be explored through some empirically grounded themes. The analysis is based on experiences from participation in a PhD program, where learning study was used as a method and variation theory was the main theoretical framework. One learning study was focusing on creative writing in primary school and the other was focusing on historical primary source analysis in upper secondary school. Findings: The first question is addressed through the following themes: choosing and identifying research problems; planning and conducting research lessons; analyzing research lessons and students' learning; and process of self-reflection, and the second question through: teaching as an object of research; to use and develop theories; and communication and review in research. The findings indicate that learning study is a practice-based research approach where teaching experience and academic skills are intertwined in many ways. Both approaches bring opportunities as well as challenges. Originality/value: The paper is expected to contribute insights and knowledge about the advantages, as well as hindrances to overcome, for teacher-researchers who use learning study as a research method. The results can also be related to the performing of action research in teachers' classroom practice.